2009
DOI: 10.1007/s00436-009-1414-0
|View full text |Cite
|
Sign up to set email alerts
|

The European vectors of Bluetongue virus: are there species complexes, single species or races in Culicoides obsoletus and C. pulicaris detectable by sequencing ITS-1, ITS-2 and 18S-rDNA?

Abstract: When studying the vectorship of Culicoides species during the outbreak of Bluetongue disease (BTD) in Central Europe, the question arose whether the most common species and additionally proven vectors of BTV (C. obsoletus and C. pulicaris) are definitive species or do they belong to so-called complexes, since the determination based on morphological criteria is not very significant and knowledge on the life cycles is poor or even absent. Therefore, the present molecular biological study on their ITS-1, ITS-2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
4
15
0
1
Order By: Relevance
“…Kiehl et al (2009) carried out phylogenetic studies using different molecular markers on Palaearctic species and according to base differences concluded that two synonymies are present within the Obsoletus group. The authors stated that C. scoticus Downes and Kettle 1952 and C. montanus Shakirzjanova 1952 are a "race" of C. obsoletus (Meigen 1818) and should not be considered as separate species.…”
Section: Introductionmentioning
confidence: 99%
“…Kiehl et al (2009) carried out phylogenetic studies using different molecular markers on Palaearctic species and according to base differences concluded that two synonymies are present within the Obsoletus group. The authors stated that C. scoticus Downes and Kettle 1952 and C. montanus Shakirzjanova 1952 are a "race" of C. obsoletus (Meigen 1818) and should not be considered as separate species.…”
Section: Introductionmentioning
confidence: 99%
“…For the molecular detection and identification of Culicoides specimens, many PCR-based methods have been developed. The ITS-1 gene of Culicoides genome is suggested as a reliable and useful region for diagnosis and genetic investigations of midges (Cetre-Sossah et al 2004;Kiehl et al 2009a;Perrin et al 2006). The ITS-1 gene was also used as a reliable marker in correct molecular identification of Culicoides species in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular tools and markers have been developed for identification and phylogenetic analysis describing their genetic relationship. The first internal transcribed spacer (ITS-1) gene of ribosomal DNA (rDNA) is suggested as good phylogenetic molecular marker useful for phylogenetic studies (Cetre-Sossah et al 2004;Kiehl et al 2009a;Perrin et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Baldet et al (2008) postulated that it is impossible to separate the females of C. obsoletus and C. scoticus by morphological characters, and in some reports, the four species or at least the females of C. obsoletus and C. scoticus are described or grouped as one entity (Mehlhorn et al 2008;Meiswinkel et al 2007) and suggested to be races rather than species (Kiehl et al 2009). Morphological and molecular characters together support the existence of C. obsoletus and C. scoticus as two taxa (Garros et al 2010), as previously confirmed with a phylogenetic tree-based study (Nolan et al 2007).…”
Section: Introductionmentioning
confidence: 97%